Zero Trust Security in Computer Networks: A Bibliometric Mapping of Research Evolution - Loso Judijanto; Arnes Yuli Vandika; Nanny Mayasari; I Wayan Karang Utama (West Science Interdisciplinary Studies, 2026)
The rapid transformation of digital infrastructures, cloud computing adoption, Internet of Things (IoT) expansion, and increasing cyber threats have accelerated the need for advanced cybersecurity approaches beyond traditional perimeter-based defense mechanisms. Zero Trust Security has emerged as a strategic security paradigm that emphasizes continuous verification, identity-based access control, and adaptive protection across modern computer networks. This study aims to analyze the evolution, intellectual structure, and emerging research trends of Zero Trust Security through a bibliometric mapping approach. Data were collected from a scientific database and analyzed using bibliometric techniques, including performance analysis, keyword co-occurrence analysis, citation analysis, co-authorship analysis, institutional collaboration analysis, and country collaboration mapping using VOSviewer. The findings reveal that Zero Trust Security research has experienced significant development, with network security, cybersecurity, and Zero Trust Architecture emerging as central research themes. Influential studies highlight the importance of authentication mechanisms, intrusion detection systems, blockchain integration, and secure architectures for cloud, 5G, and IoT environments. The thematic evolution indicates a shift from foundational security mechanisms toward intelligent and adaptive solutions involving machine learning, deep learning, federated learning, and privacy-preserving technologies. Collaboration analysis shows that research contributions are dominated by countries such as the United States, India, and China, while global cooperation continues to expand. This study contributes to the cybersecurity literature by providing a comprehensive overview of Zero Trust Security development and identifying future research directions toward intelligent, scalable, and resilient security frameworks for next-generation computer networks.